A STUDY ON THE ABILITY OF THE SECOND GRADE STUDENTS OF SMPN 6 TAMBUSAI IN WRITING DESCRIPTIVE TEXTS - Purba, Paska Rowarni; Delfi, Syofia; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study is to find out the ability of the second grade students of SMPN 6 Tambusai in writing descriptive texts. In this research, the data was obtained from students? writing scores. The test is in the form of an essay, because the test required the respondents to give the answer in the form of written descriptive text. There are five components of writing: grammar, organizing ideas, vocabulary, fluency, and mechanics (Harris : 1974). The writer analyzed the ability of the second year students based on five category: excellent, good, mediocre, poor, and very poor. The participants in this study are 30 students from VIII A of SMPN 6 Tambusai. The result of this study described that a number of students faced a problem in Grammar. Organization is the highest average score. Based on these findings, it can be concluded that the ability of the second year students of SMPN 6 Tambusai is in mediocre level and the students faced some difficulties in writing descriptive texts.Key Words: Writing Ability, Descriptive Text